Ultrasonicated Synthesis of N-Benzyl-2,3-substituted Morpholines, via the Mitsunobu Diol Cyclisation - B. Jayachandra Reddy; M. C. Somasekhara Reddy (E-Journal of Chemistry)
A facile five step synthesis of N-benzyl-2,3-substituted morpholines (i-iii) was performed. The key steps were microwave assisted Friedel-crafts acylation and diol cyclization carried out via an ultra sonication of Mitsunobu reaction using DEAD (diethylazodicarboxylate), TPP in THF for 1 h. The morpholine products were generated as diasteriomers (ii andiii) which has been separated by the column chromatography to good yield. The structure of compounds (i-iii) has been characterized by the spectral and chemical studies.